2004
DOI: 10.1074/jbc.m311222200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Role of Bovine Upstream Stimulatory Factor 1 and 2 in the Regulation of the Prostaglandin G/H Synthase-2 Promoter in Granulosa Cells

Abstract: The transcriptional activation of the prostaglandin G/H synthase-2 (PGHS-2) gene in granulosa cells is required for ovulation. To directly study the ability of upstream stimulatory factor 1 (USF1) and USF2 to trans-activate the bovine PGHS-2 promoter in granulosa cells, USF1 or USF2 expression vectors were cotransfected with the PGHS-2/luciferase (LUC) chimeric construct, ؊149/؊2PGHS-2.LUC. Results revealed that overexpression of USF1 or USF2 caused a marked and significant increase in basal and forskolin-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 63 publications
2
37
0
Order By: Relevance
“…The overlapping CRE-1 and E-box element of the human promoter have been studied in transfected LPS-stimulated RAW264.7 macrophages (14) and shown to be involved in stimulation of COX-2 transcription. The E-box element has also been shown to act as a positive regulatory element for COX-2 expression in bovine granulosa cells (15) and in PMA-treated human gastric epithelial cells (16). Although previous studies have suggested that the CRE-1, C/EBP, and NF-B sites are involved in regulating COX-2 formation in RAW264.7 cells, no other cis-acting elements have been shown to be functional.…”
mentioning
confidence: 94%
“…The overlapping CRE-1 and E-box element of the human promoter have been studied in transfected LPS-stimulated RAW264.7 macrophages (14) and shown to be involved in stimulation of COX-2 transcription. The E-box element has also been shown to act as a positive regulatory element for COX-2 expression in bovine granulosa cells (15) and in PMA-treated human gastric epithelial cells (16). Although previous studies have suggested that the CRE-1, C/EBP, and NF-B sites are involved in regulating COX-2 formation in RAW264.7 cells, no other cis-acting elements have been shown to be functional.…”
mentioning
confidence: 94%
“…Furthermore, previous studies have shown that PACAP increases the production of progesterone and PGE2 in the ovary of crested newt, Triturus carnifex (Zhong & Kasson 1994, Gobbetti et al 1997, Gras et al 1999, Ko et al 1999. In the present work, we used primary granulosa cell cultures that have been previously established as a valuable in vitro model to study the regulation of several bovine genes, including PGHS-2 and cPLA2, and the production of PGE2 recapitulating results observed in vivo (Liu et al 1999, Sayasith et al 2004, Diouf et al 2006. A similar in vitro model was employed in rodents to study the gonadotropin-dependent regulation of PACAP and its role in the suppression of follicle apoptosis (Lee et al 1999.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that incubation of preovulatory follicles or granulosa cells with PACAP markedly stimulates cAMP production and amplifies FSH stimulation of cAMP, suggesting that PACAP may act as a mediator for LH during ovulation (Tornell et al 1988, Heindel et al 1996, Cecconi et al 2004. It is known that the preovulatory LH surge induces follicular cAMP production, causing a transient increase of several enzymes and receptors, such as PGHS-2, PR and ADAMTS-1, and production of PGE2 (Richards et al 2002, Sirois et al 2004. Furthermore, previous studies have shown that PACAP increases the production of progesterone and PGE2 in the ovary of crested newt, Triturus carnifex (Zhong & Kasson 1994, Gobbetti et al 1997, Gras et al 1999, Ko et al 1999.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations